IMPROVING EMOTIONAL WELL-BEING THROUGH NATURE - Amir Hamzah, Ikhwan; Nik Hashim, Nik Nur Wahidah; Ahmad Basri, Nadzirah (PERINTIS eJournal, 2022)
Nature may be used as a treatment method for patients with mental disorders which has yet to be implemented despite numerous evidence showing that being in touch with nature links to increased happiness, positive affect, positive social interactions, and a sense of meaning and purpose in life, as well as reduced mental distress. This project focuses on demonstrating the benefits of nature towards improving emotional well-being of people based on the detection of Electrodermal Activity (EDA). EDA signals will be collected from the controlled and experimental participants for the identification of nature’s positive impact towards participants’ mental well-being. Raw signals will require pre-processing and feature extraction which will use an open-source Python toolkit called PyEDA. The project will also incorporate machine learning for EDA signal classification which also utilizes python open-source software. The results will be observed and studied based on its accuracy in classifying the EDA signals between the controlled and experimental conditions. This project will be heading towards improving mental health treatment by proving that incorporating the world’s most abundant resources, nature together with the incorporation of biosensors for mental health detection will help close the gap between mental health patients and clinicians.